Analisis Penerapan Metode Penyusutan Aset Tetap Dan Pengaruhnya Terhadap Laba Perusahaan Pada PT. Enseval Putera Megatrading, Tbk Cabang Manado - Destrina T A Siep; Alpindos Towouela; Sintia N Korompis; Raykes H Tuerah; Dominikus Andreo M (CV. Ulil Albab Corp, 2024)
PT. Enseval Putera Megatrading Tbk, Manado Branch is a distributor company that sells pharmaceutical, food, and beauty products. PT. Enseval Putera Megatrading, Tbk Manado Branch uses the straight-line depreciation method to depreciate all of its fixed assets. This straight-line depreciation method is in accordance with Financial Accounting Standard (FAS) No. 16 on Fixed Assets. This study aims to analyze the application of the fixed asset depreciation method and its effect on company profit at PT. Enseval Putera Megatrading, Tbk Manado Branch. The research method used is a qualitative method . Primary data is obtained through interviews and observations, while secondary data is obtained from the company's financial statements. This study provides results on how to calculate depreciation of fixed assets if using other methods such as declining balance and sum-of-the-years' digits, and how each method affects the tax burden, especially in this study, on the profit generated. This study recommends that PT. Enseval Putera Megatrading, Tbk Manado Branch consider using other depreciation methods that can provide greater benefits to the company.